Lithuania and European Union: Tax Harmonization - Stačiokas, Romas (Ekonomika, 2003)
Article contains analysis of issues related with radical reformation of Lithuanian tax system. harmonization its social and economical consequences with EU taxation practice and applicable tax legal attitudes. Lithuanian tax legislation must agree with legal acts and taxation directives of European Union, as it is stated in Lithuanian negotiation position “Taxes” (10th paragraph of negotiation). After implementation of tax policy means adequate to EU, the development of private and public undertakings will grow, satisfaction of material, everyday and cultural needs of inhabitants will be improved. This is the reason why decisive state and local authority institutions will have to reduce the tax load and create effective mechanism of taxing income redistribution over state and local authorities’ budgets. These institutions will also have to review applications of exceptions for different form., business organizations or profit (income). Therefore continuous taxation environment will develop and practical possibilities for reducing tax rates of juridical and physical bodies will appear. This of course will influence accession of state and local authorities’ budgetary income from tax and charges.The more especially as according to the forecast of Lithuanian consolidated gross country budget economy program (until the admission to the European Union) income of the year 2003 were 28.9 percent, expenses - 30.4 percent (corrected regarding expenses of pension reform) and the fiscal deficit - 1.5 percent of Gross Domestic Product (GDP). These lower (comparing with rates of other European countries) rates of revenue and expenses of Lithuanian consolidated budget indicate that economical performance and financial discipline may be improved. Due to the incomplete economical and financial performance huge amounts of income do not pass to the National budget (NB) and other budgets. Free and fair competition is perverted. Basic results of Lithuanian Republic financial statements arc different. During last five years (including year 2003) proportion of NB and GDP has not reached level of year 1998. Though several governments of Lithuanian Republic and Parliament have changed, but there have not been achieved better result, on budget formation and especially on its performing.On the basis of performed analysis, there have been conclusions, that in the point of tax harmonization view European Union is legal formation of limited power. It has delegation to act solo only if it concerns issues of taxation, which have been transmitted to EU by its member countries. This conception in taxation sphere is very heterogeneous, because respective treaties fix unequal legal base for coordination and unification of direct and non direct taxes of EU member countries. European Council mainly has the right to initiate legal acts and EU directives, other legal documents required for coordination of turnover, excise duties and other non direct taxation forms. Although European Council has juridical right to initiate legal acts needful for harmonization of non direct taxes, there is several EU directives and conventions regulating principles of direct taxation in European Union.Since year 2001 cardinal tax reform has been implemented in Lithuania taking into consideration adequate tax policy means and requirements of EU. Law on Value added tax (VAT) and excise duties are reconci1cd with acquis communataire requirement of European Union and requirements of international organizations. Law on income tax of individuals has came into force. This law has changed Law on income and assets of physical persons. Law on profit tax has changed law on profit tax of juridical persons. It has legitimated almost in half less rate of profit tax, simplified method of revenue and expense recognition and canceled baseless taxable privileges and exceptions. New tax laws in pursuance of Lithuanian tax reform do not mean enlargement of tax load. Contrarily, the purpose of tax reform is the reduction of gross tax load and positive influence of tax harmonization process (according EU requirements).